Effects of Calcination Temperature of Naturally Occurring Absorbents on Drinking Water Defluoridation - Mndolwa, Brenda A.; Mtalo, Felix W. (Tanzania Journal of Engineering and Technology, 2021)
Currently, in Tanzania, fluoride removal from drinking water is treated mostly using the bone char method. The method has poor acceptability in some religious communities and also causes water quality deterioration in taste and odour if the bones are not properly prepared. The use of local natural adsorbents as an alternative is feasible with limitations of high levels of other impurities in treated water. Locally available gypsum, magnesite and bauxite were converted to adsorbents through calcination. The study was conducted to determine the removal efficiency, best calcination temperature and composite ratio of the three adsorbents for the removal of fluoride from natural drinking water with fluoride concentration as high as 16.7 mg/L. The adsorbent materials were calcined at different temperatures ranging between 3500C and 6000C. Batch experiments were performed and samples were collected at different contact time intervals of 2 minutes to 60 minutes, and residual fluoride was determined. Bauxite had the highest fluoride removal efficiency compared to gypsum and magnesite. The best calcination temperatures were 3500C, 4000C, 6000C for gypsum, bauxite and magnesite, respectively. The best calcination temperatures were used to prepare composites at different ratios of 1:2:3, 2:3:1 and 3:2:1, bauxite: gypsum: magnesite respectively. All the ratios gave low sulphate and iron as impurities within the recommended standards. The composites lowered fluoride concentration level to 1.53 mg/L, 2.07 mg/L, 2.60 mg/L for 1:2:3, 2:3:1, 3:2:1 ratios, respectively. In conclusion the study reveals that, it is possible for composites made of adsorbent calcinated at different optimum temperatures to give good results in fluoride removal from drinking water, as well as standard pH, iron and sulphate values in treated water. Keywords: Fluoride, Bauxite, gypsum, magnesite, composite ratio, adsorbent.